Pengembangan Media Diorama Water Cycle pada Pembelajaran IPAS di Kelas V SD Negeri 08 Sungai Raya - Suryaningsih, Nining; Setyowati, Dessy; Hertati, Elvani (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to develop and test the feasibility of a water cycle diorama medium in teaching science and mathematics material on the water cycle in Grade V at SDN 08 Sungai Raya. The problem faced is the low utilisation of visual media, making it difficult for students to understand the water cycle process concretely. This study used the Research and Development (R&D) method with the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. Data were obtained through validation by media experts, subject matter experts, and practitioners, as well as individual trials with students. The validation results showed very high feasibility with a percentage of 100% by media experts, 100% by practitioners, and 80% by subject matter experts, while individual trials obtained a result of 96.7%. Based on these results, the water cycle diorama media was declared very feasible and effective for use in science education because it helps students understand the concept of the water cycle more easily, attractively, and interactively.